2012
DOI: 10.1007/s00122-012-1990-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the quantitative trait loci (QTL) underlying water soluble protein content in soybean

Abstract: Water soluble protein content (SPC) plays an important role in the functional efficacy of protein in food products. Therefore, for the identification of quantitative trait loci (QTL) associated with SPC, 212 F(2:9) lines of the recombinant inbred line (RIL) population derived from the cross of ZDD09454 × Yudou12 were grown along with the parents, in six different environments (location × year) to determine inheritance and map solubility-related genes. A linkage map comprising of 301 SSR markers covering 3,576.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 35 publications
4
40
0
1
Order By: Relevance
“…It is important to note that the WSPC-specific signal (around AX-94048210 on Gm08) that was identified across all environments by GWAS was also previously identified associated with soybean WSPC 8, 13 . This region affecting soybean WSPC was stably identified across environments and could explain 19.3% (ranged from 8.7 to 33.8%) of phenotypic variance, with an average increase of 38.2% of WSPC per T allele (Fig.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…It is important to note that the WSPC-specific signal (around AX-94048210 on Gm08) that was identified across all environments by GWAS was also previously identified associated with soybean WSPC 8, 13 . This region affecting soybean WSPC was stably identified across environments and could explain 19.3% (ranged from 8.7 to 33.8%) of phenotypic variance, with an average increase of 38.2% of WSPC per T allele (Fig.…”
Section: Resultsmentioning
confidence: 71%
“…In addition, some studies showed that the amino acid permease in Vicia narbonensis and pea can increase seed storage proteins 11, 12 . Recently, QTLs underlying WSPC have been identified in soybean 8, 13 . Despite a preliminary understanding of the soybean WSPC obtained, the molecular basis of natural variation in WSPC biosynthesis has not been fully elucidated because the QTL resolution is limited by the low density of molecular markers used in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…QPor20-1 mapped with a smaller confidence interval at the central part of many published QTLs, which were also identified by Diers et al (1992), Sebolt et al (2000), Brummer et al (1997), Tajuddin et al (2003), Chung et al (2003), Nichols et al (2006), Lu et al (2013) and Pandurangan et al (2012) in the classic population. These QTLs were detected in at least one macro-environment that corresponded to the combination of year and location (Palomeque et al 2009), and align consistently with previous research.…”
Section: Main Effects Of the Stable Additive Qtl Analysismentioning
confidence: 91%
“…Contents of soybean seed protein [24] and oil [25] have also been previously studied by meta-analysis with 107 and 121 QTLs, respectively. However, in recent years numerous additional QTL mapping studies for these two traits have rapidly accumulated [10,11,12,13,26,27,28,29,30,31,32,33,34,35,36], as well as, QTL studies on the amino acid and fatty acid compositions of soybean seed protein and oil [37,38,39,40,41,42,43]. Thus, with a nearly three-fold increase in the number of QTL available, a new meta-analysis for seed protein and oil contents which includes recent QTLs for seed protein and oil content as well as seed amino acid and fatty acids profiles is timely.…”
Section: Introductionmentioning
confidence: 99%